Antistatic resin composition, and transport container obtained by using the same

The antistatic resin composition, featuring a polymer compound and alkali metal salts or ionic liquids, addresses the limitations of conventional materials by providing superior antistatic performance, sustainability, and solvent resistance for conveying containers.

JP2025038580APending Publication Date: 2025-03-19ADEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023145285
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-07
Publication Date
2025-03-19

AI Technical Summary

Technical Problem

Conventional conductive materials used in antistatic resin compositions for conveying containers have insufficient antistatic properties and persistence, and are compromised by solvent exposure, leading to deteriorated performance.

Method used

The development of an antistatic resin composition incorporating a specific polymer compound derived from the reaction of a diol, a dicarboxylic acid, a polyether with hydroxyl groups, and an epoxy compound, combined with alkali metal salts or ionic liquids, to enhance antistatic performance, sustainability, and solvent resistance.

Benefits of technology

The antistatic resin composition achieves excellent antistatic properties, sustainability, and solvent resistance, effectively preventing static buildup and maintaining performance even in the presence of solvents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038580000001
    Figure 2025038580000001
  • Figure 2025038580000002
    Figure 2025038580000002
  • Figure 2025038580000003
    Figure 2025038580000003
Patent Text Reader

Abstract

To provide an antistatic resin composition which has excellent antistatic property and its sustainability, is excellent in solvent resistance, and is suitable for a transport container, and a transport container obtained by using the antistatic resin composition.SOLUTION: An antistatic resin composition contains, with respect to 100 pts.mass of a polyolefin-based resin, 2 to 35 pts.mass of the following component (X), and 0.1 to 5.0 pts.mass of the following component (Y). Component (X): an antistatic agent containing one or more polymer compounds (E) obtained by reaction of diol (a1), a dicarboxylic acid (a2), polyether (b) having hydroxyl groups at both terminals, and an epoxy compound (D) having two or more epoxy groups, in which the polyether (b) having the hydroxyl groups at both of the terminals is polyethylene glycol (b1) and polytetramethylene glycol (b2), a ratio of the polytetramethylene glycol (b2) is 10 to 80 mol% with respect to the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Y): one or more kinds selected from the group consisting of a salt (F) of alkali metal and an ionic liquid (G).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an antistatic resin composition (hereinafter also simply referred to as a "resin composition") and a transport container using the same, and more particularly to an antistatic resin composition suitable for a transport container, which has excellent antistatic performance and its durability, and excellent solvent resistance, and to a transport container using the same. [Background technology]

[0002] Industrial containers are used to transport liquids and powders, such as industrial materials, solvents, resins, feed, chemicals, food, and medicines. In particular, bulk containers (also called intermediate bulk containers or IBC containers) are widely used (for example, Patent Document 1). Polyolefin resins such as polyethylene are used for transport containers such as bulk containers. Because polyolefin resins have electrical insulation properties, they are easily charged by friction, etc. This can lead to the adhesion of dust due to charging, and if the contents are flammable, there is a risk of explosion or fire. For this reason, it has been proposed to mix conductive materials such as metals into polyolefin resins (see, for example, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Special Publication No. 2017-518926 [Patent Document 2] Special Publication No. 2003-526583 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the conventional conductive material formulation did not provide sufficient antistatic properties and their durability. In addition, in containers for transporting solvents such as organic solvents, there was a problem that the antistatic properties deteriorated due to the influence of the solvent during storage and transport. Therefore, an object of the present invention is to provide an antistatic resin composition which has excellent antistatic properties and their durability, and is also excellent in solvent resistance, and is suitable for use as a transport container, and a transport container using the same. [Means for solving the problem]

[0005] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by combining, in a predetermined ratio, one or more antistatic polymeric compounds having a specific structure with one or more compounds selected from the group consisting of alkali metal salts and ionic liquids, and have thus completed the present invention.

[0006] That is, the antistatic resin composition of the present invention is an antistatic resin composition containing 2 to 35 parts by mass of the following component (X) and 0.1 to 5.0 parts by mass of the following component (Y) per 100 parts by mass of a polyolefin resin. Component (X): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0007] In the antistatic resin composition of the present invention, the polymer compound (E) is preferably obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.

[0008] In the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.

[0009] Furthermore, in the antistatic resin composition of the present invention, it is preferable that the polymer compound (E) has a structure in which the block polymer (C) having carboxyl groups at both ends and formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds is bonded to the epoxy compound (D) via an ester bond.

[0010] In the antistatic resin composition of the present invention, the epoxy compound (D) of the polymer compound (E) is preferably polypropylene glycol diglycidyl ether. The transport container of the present invention is characterized in that it is formed from the antistatic resin composition. The transport container of the present invention is preferably for liquids. The transport container of the present invention is preferably used for flammable liquids. The transport container of the present invention is preferably a bulk container. Effect of the Invention

[0011] According to the present invention, it is possible to provide an antistatic resin composition which has excellent antistatic properties and their durability, and is also excellent in solvent resistance, and is suitable for use as a transport container, and a transport container using the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described in detail. First, the antistatic resin composition of the present invention will be described. The resin composition of the present invention contains 2 to 35 parts by mass of the following component (X) and 0.1 to 5.0 parts by mass of the following component (Y) relative to 100 parts by mass of a polyolefin resin. Component (X): An antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0013] First, the polyolefin resin used in the present invention will be described. Examples of polyolefin resins include low-density polyethylene, linear low-density polyethylene, high-density polyethylene, homopolypropylene, random copolymer polypropylene, impact copolymer polypropylene, block copolymer polypropylene, isotactic polypropylene, syndiotactic polypropylene, hemiisotactic polypropylene, polybutene, cycloolefin polymer, stereoblock polypropylene, α-olefin polymers such as poly-3-methyl-1-butene, poly-3-methyl-1-pentene, and poly-4-methyl-1-pentene, block or random copolymers of ethylene-propylene, α-olefin copolymers such as ethylene-methyl methacrylate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, and ethylene-vinyl acetate copolymer, and further polyolefin thermoplastic elastomers, and copolymers of two or more of these may be used. Two or more of these polyolefin resins may be used.

[0014] As the polyolefin resin, polyethylene resins such as low-density polyethylene, linear low-density polyethylene, and high-density polyethylene are preferred from the viewpoints of antistatic property and its durability, and solvent resistance.

[0015] Next, the component (X) used in the present invention will be described. The component (X) of the present invention is an antistatic agent containing one or more polymer compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and the polytetramethylene glycol (b2).

[0016] In terms of the antistatic property, its durability, and solvent resistance, the polymer compound (E) related to this antistatic agent is preferably a polymer compound obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.

[0017] Further, in terms of antistatic properties and their durability, and solvent resistance, the polymer compound (E) preferably has a structure in which a polyester block (A) composed of a polyester (a) and a polyether block (B) composed of a polyether (b) having hydroxyl groups at both ends are bonded via an ester bond or an ether bond formed by the reaction of a hydroxyl group or a carboxyl group at the end of the polyester (a), a hydroxyl group at the end of the polyether (b), and an epoxy group of an epoxy compound (D) having two or more epoxy groups, or a hydroxyl group formed by the reaction of an epoxy group. Here, the hydroxyl group formed by the reaction of an epoxy group of the epoxy compound (D) is a hydroxyl group formed by the ring-opening reaction of the epoxy group of the epoxy compound (D) with a hydroxyl group or a carboxyl group.

[0018] The polyester block (A) of the polymer compound (E) is composed of a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2). The polyester (a) can be obtained by esterification of the diol (a1) with the dicarboxylic acid (a2). The diol (a1) used in the polymer compound (E) according to the present invention includes an aliphatic diol and an aromatic group-containing diol. The diol (a1) may be a mixture of two or more kinds.

[0019] Examples of aliphatic diols include 1,2-ethanediol (ethylene glycol), 1,2-propanediol (propylene glycol), 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 2-methyl-1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2,2-diethyl-1,3-propanediol (3,3-dimethylol pentane), 2-n-butyl-2-ethyl-1,3propanediol (3,3-dimethylol heptane), 3-methyl -1,5-pentanediol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-octadecanediol, 1,4-cyclohexanedimethanol, hydrogenated bisphenol A, 1,2-, 1,3- or 1,4-cyclohexanediol, cyclododecanediol, dimer diol, hydrogenated dimer diol, diethylene glycol, dipropylene glycol, triethylene glycol, etc. Among these aliphatic diols, 1,4-cyclohexanedimethanol and hydrogenated bisphenol A are preferred from the viewpoints of antistatic properties and their persistence and solvent resistance, and 1,4-cyclohexanedimethanol is more preferred. Note that, it is preferable that the aliphatic diol has hydrophobicity from the viewpoints of antistatic properties and their persistence and solvent resistance, so that the use of polyethylene glycol having hydrophilicity is not preferred.

[0020] Examples of aromatic group-containing diols include bisphenol A, 1,2-hydroxybenzene, 1,3-hydroxybenzene, 1,4-hydroxybenzene, 1,4-benzenedimethanol, ethylene oxide adduct of bisphenol A, propylene oxide adduct of bisphenol A, 1,4-bis(2-hydroxyethoxy)benzene, resorcin, polyhydroxyethyl adduct of mononuclear dihydric phenol compounds such as pyrocatechol, etc. Among these diols having aromatic groups, ethylene oxide adduct of bisphenol A and 1,4-bis(β-hydroxyethoxy)benzene are preferred. It is to be noted that aromatic diols are preferably hydrophobic in terms of antistatic properties and their durability, and solvent resistance. Among these diols, 1,4-cyclohexanedimethanol is particularly preferred from the viewpoints of antistatic properties, their durability, and solvent resistance.

[0021] The dicarboxylic acid (a2) used in the polymer compound (E) according to the present invention includes an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid. The dicarboxylic acid (a2) may be a mixture of two or more kinds.

[0022] The aliphatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0023] The aliphatic dicarboxylic acid preferably includes an aliphatic dicarboxylic acid having 2 to 20 carbon atoms, and examples thereof include oxalic acid, malonic acid, glutaric acid, methylsuccinic acid, dimethylmalonic acid, 3-methylglutaric acid, ethylsuccinic acid, isopropylmalonic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid (1,10-decanedicarboxylic acid), tridecanedioic acid, tetradecanedioic acid, hexadecanedioic acid, octadecanedioic acid, eicosanediic acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanediacetic acid, 1,3-cyclohexanediacetic acid, 1,2-cyclohexanediacetic acid, 1,1-cyclohexanediacetic acid, dimer acid, maleic acid, and fumaric acid. Among these aliphatic dicarboxylic acids, from the viewpoints of antistatic property and its durability, and solvent resistance, dicarboxylic acids having 4 to 12 carbon atoms are more preferred, and adipic acid is even more preferred.

[0024] The aromatic dicarboxylic acid used in the polymer compound (E) according to the present invention may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.). The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0025] The aromatic dicarboxylic acid is preferably an aromatic dicarboxylic acid having 8 to 20 carbon atoms, such as terephthalic acid, isophthalic acid, phthalic acid, phenylmalonic acid, homophthalic acid, phenylsuccinic acid, β-phenylglutaric acid, α-phenyladipic acid, β-phenyladipic acid, biphenyl-2,2'-dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, naphthalenedicarboxylic acid, sodium 3-sulfoisophthalate, potassium 3-sulfoisophthalate, etc. Among these aromatic dicarboxylic acids, terephthalic acid, isophthalic acid, and phthalic acid (including phthalic anhydride) are preferred, and phthalic acid (including phthalic anhydride) is more preferred, from the viewpoints of antistatic property and its durability, and solvent resistance.

[0026] As the dicarboxylic acid (a2), it is preferable to use both an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid in combination, and it is particularly preferable to use adipic acid as the aliphatic dicarboxylic acid and phthalic acid (including phthalic anhydride) as the aromatic dicarboxylic acid in combination.

[0027] Next, the polyether (b) having hydroxyl groups at both ends and the polyether block (B) of the polymer compound (E) will be described. The polyether block (B) is composed of the polyether (b) having hydroxyl groups at both ends, and the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of the polytetramethylene glycol (b2) is 10 to 80 mol% based on the total number of moles of the polyethylene glycol (b1) and the polytetramethylene glycol (b2).

[0028] The number average molecular weight of the polyethylene glycol (b1) is calculated from the measured value of the hydroxyl value, and from the viewpoints of antistatic property and its durability, and solvent resistance, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and even more preferably 1,800 to 4,000. The method for measuring the hydroxyl value and the method for calculating the number average molecular weight from the hydroxyl value are described below.

[0029] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value

[0030] <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride, 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution.

[0031] First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of xylene, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]

[0032] The number average molecular weight of the polytetramethylene glycol (b2) is calculated from the measured hydroxyl value, and from the viewpoints of antistatic property and its durability, and solvent resistance, it is preferably 400 to 8,000, more preferably 1,000 to 6,000, even more preferably 1,500 to 5,000, and still more preferably 1,800 to 4,000.

[0033] The method for measuring the hydroxyl value of polytetramethylene glycol (b2) and the method for calculating the number average molecular weight from the hydroxyl value are the same as the method for measuring the hydroxyl value of polyethylene glycol (a1) and the method for calculating the number average molecular weight from the hydroxyl value.

[0034] The ratio of polyethylene glycol (b1) and polytetramethylene glycol (b2) in the polyether (b) having hydroxyl groups at both ends is 10 to 80 mol % of polytetramethylene glycol (b2) relative to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2), and from the viewpoints of antistatic property and its durability and solvent resistance, it is preferably 15 to 70 mol %, more preferably 18 to 55 mol %, and even more preferably 20 to 50 mol %.

[0035] Next, the epoxy compound (D) having two or more epoxy groups constituting the polymer compound (E) will be described. The epoxy compound (D) used in the antistatic agent of the present invention is not particularly limited as long as it has two or more epoxy groups, and examples thereof include polyglycidyl ether compounds of mononuclear polyhydric phenol compounds such as hydroquinone, resorcin, pyrocatechol, and phloroglucinol; dihydroxynaphthalene, biphenol, methylene bisphenol (bisphenol F), methylene bis(ortho-cresol), ethylidene bisphenol, isopropylidene bisphenol (bisphenol A), isopropylidene bis(ortho-cresol), tetrabromobisphenol, and the like. Polyglyceryl esters of polynuclear polyhydric phenol compounds such as phenol A, 1,3-bis(4-hydroxycumylbenzene), 1,4-bis(4-hydroxycumylbenzene), 1,1,3-tris(4-hydroxyphenyl)butane, 1,1,2,2-tetra(4-hydroxyphenyl)ethane, thiobisphenol, sulfobisphenol, oxybisphenol, phenol novolac, orthocresol novolac, ethylphenol novolac, butylphenol novolac, octylphenol novolac, resorcinol novolac, and terpene phenol. ether compounds; polyglycidyl ethers of polyhydric alcohols such as ethylene glycol, propylene glycol, butylene glycol, hexanediol, diethylene glycol, polyethylene glycol, dipropylene glycol, polypropylene glycol, polyglycol, thiodiglycol, glycerin, trimethylolpropane, pentaerythritol, sorbitol, bisphenol A-ethylene oxide adduct, and dicyclopentadiene dimethanol; maleic acid, fumaric acid, itaconic acid, succinic acid, glutaric acid, suberic acid, adipic acid, Homopolymers or copolymers of glycidyl esters of aliphatic, aromatic or alicyclic polybasic acids, such as azelaic acid, sebacic acid, dimer acid, trimer acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, trimesic acid, pyromellitic acid, tetrahydrophthalic acid, hexahydrophthalic acid, endomethylenetetrahydrophthalic acid, and glycidyl methacrylate; epoxy compounds having a glycidylamino group, such as N,N-diglycidylaniline, bis(4-(N-methyl-N-glycidylamino)phenyl)methane, and diglycidyl orthotoluidine;Examples of epoxy compounds include cyclic olefin compounds such as vinylcyclohexene diepoxide, dicyclopentadiene diepoxide, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carboxylate, 3,4-epoxy-6-methylcyclohexylmethyl-6-methylcyclohexane carboxylate, and bis(3,4-epoxy-6-methylcyclohexylmethyl) adipate; epoxidized conjugated diene polymers such as epoxidized polybutadiene and epoxidized styrene-butadiene copolymers, heterocyclic compounds such as triglycidyl isocyanurate, and epoxidized soybean oil. These epoxy compounds may be internally crosslinked with a prepolymer of terminal isocyanate, or may be polymerized using a polyvalent active hydrogen compound (polyhydric phenol, polyamine, carbonyl group-containing compound, polyphosphate ester, etc.). Two or more of such epoxy compounds (D) may be used.;

[0036] From the viewpoints of antistatic property and its durability and solvent resistance, the epoxy compound (D) is preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, dicyclopentadiene dimethanol diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, or hexanediol diglycidyl ether, more preferably polypropylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, bisphenol F diglycidyl ether, or hydrogenated bisphenol A diglycidyl ether, and even more preferably polypropylene glycol diglycidyl ether. From the viewpoints of antistatic property and its durability and solvent resistance, the polypropylene glycol diglycidyl ether is particularly preferably polypropylene glycol diglycidyl ether represented by the following general formula (1).

[0037] [ka]

[0038] In the general formula (1), n ​​represents a number of 1 to 30. n is preferably a number of 2 to 25, and more preferably a number of 3 to 15, from the viewpoints of antistatic property and its durability, and solvent resistance.

[0039] The number average molecular weight of the polypropylene glycol diglycidyl ether is preferably from 200 to 2,000, more preferably from 250 to 1,500, and even more preferably from 300 to 1,000, from the viewpoints of antistatic property and its durability, and solvent resistance.

[0040] As the polypropylene glycol diglycidyl ether, a commercially available product may be used. Examples of commercially available products include ADEKA GLYCIROL (registered trademark) ED-506 manufactured by ADEKA CORPORATION, DENACOL (registered trademark) EX-920 and DENACOL (registered trademark) EX-931 manufactured by Nagase ChemteX Corporation, and the like.

[0041] The epoxy equivalent of the epoxy compound (D) is preferably from 70 to 2,000, more preferably from 100 to 1,000, particularly preferably from 150 to 600, from the viewpoints of antistatic property and its durability, and solvent resistance.

[0042] In terms of the antistatic properties and their durability, and solvent resistance of the present invention, a preferred polymer compound (E) is one obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, and has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which a hydroxyl group or a carboxyl group at the end of the polyester (a), a hydroxyl group at the end of the polyether (b), and an epoxy group of an epoxy compound having two or more epoxy groups, or a hydroxyl group formed by the reaction of this epoxy group, are bonded via an ester bond or an ether bond, which is formed by the reaction of these hydroxyl groups or carboxyl groups at the end of the polyester (a),

[0043] Furthermore, from the viewpoints of antistatic property, its durability, and solvent resistance, the polymer compound (E) preferably has a structure in which a block polymer (C) having carboxyl groups at both ends, which is formed by repeatedly and alternately bonding a polyester block (A) composed of a polyester (a) and a polyether block (B) composed of a polyether (b) via ester bonds, is bonded to an epoxy compound (D) via an ester bond formed by the carboxyl group of the block polymer (C) and the epoxy group of the epoxy compound (D). It is also preferable that the polymer compound (E) has a structure in which a hydroxyl group formed by ring-opening of the epoxy group in a reaction with the carboxyl group is bonded to the carboxyl group via an ester bond formed by the reaction with the carboxyl group.

[0044] The polyester (a) constituting the block of the polyester (A) according to the present invention may be any one consisting of a diol (a1) and a dicarboxylic acid (a2), and from the viewpoints of antistatic properties, their duration, and solvent resistance, preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol (a1) and the residue obtained by removing the carboxyl group of the dicarboxylic acid (a2) are bonded via an ester bond. More preferably, the polyester (a) constituting the block (A) of the polyester according to the present invention is composed of a diol, an aliphatic dicarboxylic acid, and an aromatic dicarboxylic acid, and from the viewpoints of antistatic properties, their duration, and solvent resistance, preferably has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aliphatic dicarboxylic acid are bonded via an ester bond, and also has a structure in which the residue obtained by removing the hydroxyl group of the diol and the residue obtained by removing the carboxyl group of the aromatic dicarboxylic acid are bonded via an ester bond.

[0045] From the viewpoints of antistatic property and its durability, and solvent resistance, the polyester (a) preferably has a structure having carboxyl groups at both ends. Furthermore, from the viewpoints of antistatic property and its durability, and solvent resistance, the polymerization degree of the polyester (a) is preferably in the range of 2 to 50.

[0046] The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above diol (a1) with the above dicarboxylic acid (a2) (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid).

[0047] The aliphatic dicarboxylic acid may be a derivative of an aliphatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a derivative is used to obtain polyester (a), both ends may be finally treated to give carboxyl groups, or the polyester may be directly subjected to the next reaction to obtain block polymer (C) having a structure having carboxyl groups at both ends. The aliphatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0048] The aromatic dicarboxylic acid may be a derivative of an aromatic dicarboxylic acid (e.g., an acid anhydride, an alkyl ester, an alkali metal salt, an acid halide, etc.), and when a polyester is obtained using a derivative, both ends are finally treated to form carboxyl groups, and the polyester may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends. The aromatic dicarboxylic acid and its derivative may be a mixture of two or more kinds.

[0049] When an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid are used, the molar ratio of the residue of the aliphatic dicarboxylic acid excluding the carboxyl group to the residue of the aromatic dicarboxylic acid excluding the carboxyl group in the polyester (a) is preferably 90:10 to 99.9:0.1, and more preferably 93:7 to 99.9:0.1, from the viewpoints of antistatic property, its durability, and solvent resistance.

[0050] The polyester (a) having carboxyl groups at both ends can be obtained, for example, by esterification reaction of the above-mentioned dicarboxylic acid or its derivative (preferably the above-mentioned aliphatic dicarboxylic acid or its derivative, and the above-mentioned aromatic dicarboxylic acid or its derivative) with the above-mentioned diol.

[0051] Regarding the reaction ratio of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) to diol, it is preferable to use an excess of dicarboxylic acid or derivative thereof (preferably, an aliphatic dicarboxylic acid or derivative thereof, and an aromatic dicarboxylic acid or derivative thereof) so that both ends have carboxyl groups, and it is preferable to use one mole excess relative to the diol in terms of molar ratio.

[0052] The compounding ratio of the aliphatic dicarboxylic acid or its derivative to the aromatic dicarboxylic acid or its derivative during the esterification reaction is preferably from 90:10 to 99.9:0.1, more preferably from 93:7 to 99.9:0.1, in terms of molar ratio.

[0053] Depending on the compounding ratio and reaction conditions, a polyester composed only of a diol and an aliphatic dicarboxylic acid or a polyester composed only of a diol and an aromatic dicarboxylic acid may be produced. In the present invention, however, these may be mixed into the polyester (a) and may be reacted as they are with the compound (b) to obtain the block polymer (C).

[0054] The esterification reaction may be carried out in the presence of a catalyst for accelerating the reaction. As the catalyst, a conventional catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. may be used.

[0055] In addition, when a derivative of a dicarboxylic acid (preferably an aliphatic dicarboxylic acid or an aromatic dicarboxylic acid) such as a carboxylate, a carboxylate metal salt, or a carboxylate halide is used instead of a dicarboxylic acid, the dicarboxylic acid may be reacted with a diol and then treated at both ends to give a dicarboxylic acid, or the dicarboxylic acid may be directly subjected to the next reaction for obtaining a block polymer (C) having a structure having carboxyl groups at both ends.

[0056] A suitable polyester (a) consisting of a diol and a dicarboxylic acid (preferably an aliphatic dicarboxylic acid and an aromatic dicarboxylic acid) and having carboxyl groups at both ends may be any polyester that reacts with a polyether (b) to form an ester bond and form a block polymer (C) structure, and the carboxyl groups at both ends may be protected or modified, or may be in the form of a precursor. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.

[0057] The polyether (b) having hydroxyl groups at both ends preferably reacts with the polyester (a) to form an ester bond or an ether bond, preferably an ester bond, to form a block polymer (C) structure. The hydroxyl groups at both ends may be protected or modified, or may be in the form of a precursor.

[0058] The block polymer (C) having a structure having carboxyl groups at both ends of the polymer compound (E) according to the present invention has a structure in which the block (A) composed of the above polyester (a) and the block (B) composed of the above polyether (b) are repeatedly and alternately bonded via ester bonds formed by carboxyl groups and hydroxyl groups. An example of such a block polymer (C) is one having a structure represented by the following general formula (2).

[0059] [ka]

[0060] In general formula (2), (A) represents a block composed of the polyester (a) having carboxyl groups at both ends, (B) represents a block composed of the polyether (b) having hydroxyl groups at both ends, and t represents the number of repeating units, which is preferably a number from 1 to 10 from the viewpoints of antistatic property and its durability and solvent resistance. t is more preferably a number from 1 to 7, and most preferably a number from 1 to 5.

[0061] The block polymer (C) having a structure having carboxyl groups at both ends can be obtained by polycondensation reaction of a polyester (a) having carboxyl groups at both ends and a polyether (b) having hydroxyl groups at both ends. However, it is not necessary to synthesize the block polymer (C) from the polyester (a) and the polyether (b) as long as the block polymer (C) has a structure equivalent to a structure in which the polyester (a) and the polyether (b) are repeatedly and alternately bonded via ester bonds formed by a carboxyl group and a hydroxyl group.

[0062] The reaction ratio of the polyester (a) to the polyether (b) is adjusted so that the amount of the polyester (a) is X+1 moles per mole of the polyether (b), thereby making it possible to preferably obtain a block polymer (C) having carboxyl groups at both ends.

[0063] In the reaction, after completion of the synthesis reaction of the polyester (a), the polyester (a) may not be isolated, but the polyether (b) may be added to the reaction system and reacted as is.

[0064] In the polycondensation reaction, a catalyst for promoting the esterification reaction may be used, and as the catalyst, a conventionally known catalyst such as dibutyltin oxide, tetraalkyl titanate, zirconium acetate, zinc acetate, etc. In order to suppress oxidation of the product during the reaction, an antioxidant such as a phenol-based antioxidant may be added to the reaction system.

[0065] From the viewpoints of antistatic property and its durability and solvent resistance, the polymer compound (E) according to the present invention preferably has a structure in which a block polymer (C) having a structure with carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups are bonded via an ester bond. The ester bond may be either an ester bond formed by the reaction between the carboxyl group at the end of the block polymer (C) and the epoxy group of the epoxy compound (D), or an ester bond formed by the reaction between a hydroxyl group formed by this reaction (the reaction between a carboxyl group and an epoxy group) and a carboxyl group, and it is preferable that both ester bonds are present from the viewpoints of antistatic property and its durability and solvent resistance.

[0066] Moreover, the polymer compound (E) may further contain an ester bond formed between a carboxyl group of the polyester (a) and an epoxy group of the epoxy compound (D).

[0067] Furthermore, the polymer compound (E) may contain an ester bond formed between a carboxyl group of the polyester (a) and a hydroxyl group formed by reaction of an epoxy group of the epoxy compound.

[0068] Furthermore, the polymer compound (E) may further contain an ether bond formed by a hydroxyl group of the polyester (a) or a hydroxyl group of the polyether (b) and an epoxy group of the epoxy compound (D).

[0069] In order to obtain a preferred polymer compound (E), the block polymer (C) and the epoxy compound (D) may be reacted. That is, the carboxyl group of the block polymer (C) may be reacted with the epoxy group of the epoxy compound (D). More preferably, the hydroxyl group formed from the reacted epoxy group may be reacted with the carboxyl group. The number of epoxy groups in the epoxy compound (D) is preferably 0.5 to 5 equivalents, more preferably 0.5 to 1.5 equivalents, of the number of carboxyl groups in the block polymer (C) to be reacted. The reaction may be carried out in various solvents or in a molten state.

[0070] The amount of the epoxy compound (D) having two or more epoxy groups to be reacted is preferably 0.1 to 2.0 equivalents, more preferably 0.2 to 1.5 equivalents, relative to the number of carboxyl groups in the block polymer (C) to be reacted.

[0071] In the reaction, after completion of the synthesis reaction of the block polymer (C), the epoxy compound (D) may be added to the reaction system and reacted as it is without isolating the block polymer (C). In this case, the carboxyl groups of the unreacted polyester (a) used in excess when synthesizing the block polymer (C) may react with some of the epoxy groups of the epoxy compound (D) to form ester bonds.

[0072] A preferred polymer compound (E) according to the present invention does not necessarily have to be synthesized from the block polymer (C) and the epoxy compound (D) as long as it has a structure equivalent to that of a block polymer (C) having a structure with carboxyl groups at both ends and an epoxy compound (D) having two or more epoxy groups bonded via an ester bond formed between the respective carboxyl groups and epoxy groups. The ester bond formed between a carboxyl group and an epoxy group as referred to here also includes an ester bond formed between a carboxyl group and a hydroxyl group formed from an epoxy group by reacting with the carboxyl group.

[0073] In addition, the polymer compound (E) according to the present invention may be prepared by obtaining a polyester (a) from a diol (a1) and a dicarboxylic acid (a2), and then reacting the polyester (a) with a polyether (b) and / or an epoxy compound (D) without isolating the polyester (a).

[0074] In the polymer compound (E) of the present invention, the number average molecular weight of the polyester (a) constituting the block (A) composed of the polyester (a) is, in terms of polystyrene, preferably 1,000 to 10,000, more preferably 1,500 to 8,000, and even more preferably 2,500 to 7,500, from the viewpoints of antistatic property and its durability, and solvent resistance. If the number average molecular weight is less than 1,000, the storage stability may be poor, and if it exceeds 10,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to a long reaction time.

[0075] The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is shown below. <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL

[0076] Furthermore, the number average molecular weight of the block polymer (C) having a structure with carboxyl groups at both ends in the polymer compound (E) is preferably 5,000 to 50,000, more preferably 10,000 to 45,000, in terms of polystyrene, from the viewpoints of antistatic property and its durability, and solvent resistance. If the number average molecular weight is less than 5,000, the storage stability may be poor, and if it exceeds 50,000, the reaction to obtain the polymer compound (E) may take a long time, which may result in poor economic efficiency, or the obtained polymer compound may become discolored due to a long reaction time. The method for measuring the number average molecular weight in terms of polystyrene is preferably gel permeation chromatography (GPC), and the measuring method is as described above.

[0077] In the antistatic resin composition of the present invention, the content of the (X) component is 2 to 35 parts by mass relative to 100 parts by mass of the polyolefin resin. From the viewpoints of antistatic property and its durability, and solvent resistance, the content is preferably 8 to 30 parts by mass, and more preferably 15 to 25 parts by mass.

[0078] Next, the component (Y) of the present invention will be described. The component (Y) of the present invention is one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

[0079] Hereinafter, the alkali metal salt (F) will be described first. Examples of the alkali metal salt (F) include salts of organic acids or inorganic acids, and examples of the alkali metal include lithium, sodium, potassium, cesium, and rubidium. Examples of the organic acid include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of the inorganic acid include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid. Among them, in terms of antistatic property and its durability, solvent resistance, and safety to living bodies and the environment, lithium, sodium, and potassium salts are preferred, and sodium is more preferred. In terms of antistatic property and its durability, and solvent resistance, acetic acid salts, perchloric acid salts, p-toluenesulfonic acid salts, and dodecylbenzenesulfonic acid salts are preferred, and dodecylbenzenesulfonic acid salts are more preferred. The alkali metal salts may be two or more kinds.

[0080] Specific examples of the alkali metal salt (F) include lithium acetate, sodium acetate, potassium acetate, lithium chloride, sodium chloride, potassium chloride, lithium phosphate, sodium phosphate, potassium phosphate, lithium sulfate, sodium sulfate, lithium perchlorate, sodium perchlorate, potassium perchlorate, lithium p-toluenesulfonate, sodium p-toluenesulfonate, potassium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, etc. Among these, from the viewpoints of antistatic property and its durability, solvent resistance, and safety to living bodies and the environment, preferred are lithium p-toluenesulfonate, sodium p-toluenesulfonate, lithium dodecylbenzenesulfonate, sodium dodecylbenzenesulfonate, etc., and most preferred is sodium dodecylbenzenesulfonate.

[0081] Next, the ionic liquid (G) will be described. Examples of ionic liquids include room-temperature molten salts having a melting point of 100°C or less, at least one of the cations or anions constituting the ionic liquid being an organic ion, and having an initial conductivity of 1 to 200 ms / cm, preferably 10 to 200 ms / cm, such as those described in WO 95 / 15572.

[0082] Examples of the cations constituting the ionic liquid include cations selected from the group consisting of amidinium, pyridinium, pyrazolium and guanidinium cations. Among these, examples of the amidinium cation include the following: (1) Imidazolinium cation Examples of the imidazolinium include those having 5 to 15 carbon atoms, such as 1,2,3,4-tetramethylimidazolinium and 1,3-dimethylimidazolinium; (2) Imidazolium cation Examples of the imidazolium derivatives include those having 5 to 15 carbon atoms, such as 1,3-dimethylimidazolium and 1-ethyl-3-methylimidazolium; (3) Tetrahydropyrimidinium cation Examples of the aryl group include those having 6 to 15 carbon atoms, such as 1,3-dimethyl-1,4,5,6-tetrahydropyrimidinium and 1,2,3,4-tetramethyl-1,4,5,6-tetrahydropyrimidinium; (4) Dihydropyrimidinium cation Examples of the alkyl group include those having 6 to 20 carbon atoms, such as 1,3-dimethyl-1,4-dihydropyrimidinium, 1,3-dimethyl-1,6-dihydropyrimidinium, 8-methyl-1,8-diazabicyclo[5,4,0]-7,9-undecadienium, and 8-methyl-1,8-diazabicyclo[5,4,0]-7,10-undecadienium. The pyridinium cation may be one having 6 to 20 carbon atoms, such as 3-methyl-1-propylpyridinium and 1-butyl-3,4-dimethylpyridinium.

[0083] The pyrazolium cation may be one having 5 to 15 carbon atoms, such as 1,2-dimethylpyrazolium or 1-n-butyl-2-methylpyrazolium.

[0084] The guanidinium cations include the following: (1) Guanidinium cation with an imidazolinium skeleton Examples of the imidazolium salt include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolinium and 2-diethylamino-1,3,4-trimethylimidazolinium; (2) Guanidinium cation with an imidazolium skeleton Examples of the imidazolium derivatives include those having 8 to 15 carbon atoms, such as 2-dimethylamino-1,3,4-trimethylimidazolium and 2-diethylamino-1,3,4-trimethylimidazolium; (3) Guanidinium cation having a tetrahydropyrimidinium skeleton Examples of the alkyl group include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4,5,6-tetrahydropyrimidinium and 2-diethylamino-1,3-dimethyl-4-ethyl-1,4,5,6-tetrahydropyrimidinium; (4) Guanidinium cation having a dihydropyrimidinium skeleton Examples thereof include those having 10 to 20 carbon atoms, such as 2-dimethylamino-1,3,4-trimethyl-1,4-dihydropyrimidinium, 2-dimethylamino-1,3,4-trimethyl-1,6-dihydropyrimidinium, 2-diethylamino-1,3-dimethyl-4-ethyl-1,4-dihydropyrimidinium, and 2-diethylamino-1,3-dimethyl-4-ethyl-1,6-dihydropyrimidinium.

[0085] The above cations may be used alone or in combination of two or more. Among these, from the viewpoints of antistatic properties and their durability, and solvent resistance, the amidinium cation is preferred, the imidazolium cation is more preferred, and the 1-ethyl-3-methylimidazolium cation is particularly preferred.

[0086] In the ionic liquid, examples of organic or inorganic acids constituting the anion include the following. Examples of organic acids include carboxylic acids, sulfuric esters, sulfonic acids, and phosphoric esters; examples of inorganic acids include superacids (e.g., borofluoroacid, tetrafluoroboric acid, perchloric acid, hexafluorophosphoric acid, hexafluoroantimonic acid, and hexafluoroarsenic acid), phosphoric acid, and boric acid. The above organic acids and inorganic acids may be used alone or in combination of two or more.

[0087] Of the above organic acids and inorganic acids, preferred from the viewpoints of the antistatic property and its durability, and solvent resistance of the ionic liquid are acids which form conjugate bases of super strong acids, anions other than the conjugate bases of super strong acids, and mixtures thereof, and which have a Hamett acidity function (-H0) of 12 to 100 for the anions constituting the ionic liquid.

[0088] Examples of anions other than the conjugate base of a superacid include halogen (e.g., fluorine, chlorine, and bromine) ions, alkyl (having 1 to 12 carbon atoms) benzenesulfonic acid (e.g., p-toluenesulfonic acid and dodecylbenzenesulfonic acid) ions, and poly(n=1 to 25) fluoroalkanesulfonic acid (e.g., undecafluoropentanesulfonic acid) ions.

[0089] In addition, examples of the super strong acid include protonic acids and those derived from a combination of a protonic acid and a Lewis acid, and mixtures thereof. Examples of the protonic acid as the super strong acid include bis(trifluoromethylsulfonyl)imide acid, bis(pentafluoroethylsulfonyl)imide acid, tris(trifluoromethylsulfonyl)methane, perchloric acid, fluorosulfonic acid, alkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., methanesulfonic acid, dodecanesulfonic acid, etc.), poly(n=1 to 30)fluoroalkane (having 1 to 30 carbon atoms)sulfonic acid (e.g., trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, heptafluoropropanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, and tridecafluorohexanesulfonic acid), borofluoric acid, and tetrafluoroboric acid. Among these, preferred from the viewpoint of ease of synthesis are borofluoroacid, trifluoromethanesulfonic acid, bis(trifluoromethanesulfonyl)imidic acid and bis(pentafluoroethylsulfonyl)imidic acid.

[0090] Examples of protonic acids used in combination with the Lewis acid include hydrogen halides (e.g., hydrogen fluoride, hydrogen chloride, hydrogen bromide, and hydrogen iodide), perchloric acid, fluorosulfonic acid, methanesulfonic acid, trifluoromethanesulfonic acid, pentafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, undecafluoropentanesulfonic acid, tridecafluorohexanesulfonic acid, and mixtures thereof. Among these, hydrogen fluoride is preferred from the viewpoint of the initial conductivity of the ionic liquid.

[0091] Examples of Lewis acids include boron trifluoride, phosphorus pentafluoride, antimony pentafluoride, arsenic pentafluoride, tantalum pentafluoride, and mixtures thereof. Among these, boron trifluoride and phosphorus pentafluoride are preferred from the viewpoint of the initial conductivity of the ionic liquid.

[0092] The combination of the protonic acid and the Lewis acid is arbitrary, and examples of super strong acids formed by these combinations include tetrafluoroboric acid, hexafluorophosphoric acid, hexafluorotantalic acid, hexafluoroantimonic acid, hexafluorotantalum sulfonic acid, tetrafluoroboric acid, hexafluorophosphoric acid, chlorotrifluoroboric acid, hexafluoroarsenic acid, and mixtures thereof. Of the above anions, from the viewpoint of the antistatic properties of the ionic liquid and their durability, preferred are the conjugate bases of super strong acids (super strong acids made of protonic acids and super strong acids made of a combination of a protonic acid and a Lewis acid), and more preferred are the conjugate bases of super strong acids made of protonic acids and super strong acids made of a protonic acid, boron trifluoride and / or phosphorus pentafluoride.

[0093] Among ionic liquids, from the viewpoints of antistatic properties and their durability, and solvent resistance, preferred are ionic liquids having an amidinium cation, more preferred are ionic liquids having a 1-ethyl-3-methylimidazolium cation, and particularly preferred is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide. In the component (Y) of the present invention, the alkali metal salt (F) and the ionic liquid (G) may be used in combination.

[0094] In the antistatic resin composition of the present invention, the content of the (Y) component is 0.1 to 5.0 parts by mass relative to 100 parts by mass of the polyolefin resin, and from the viewpoints of antistatic property and its durability and solvent resistance, it is preferably 0.5 to 3.5 parts by mass, more preferably 0.8 to 2.5 parts by mass. When the (Y) component is blended with the polyolefin resin, it may be blended directly, or the (Y) component may be added to the reaction system during the synthesis reaction of the polymer compound (E) which is the (X) component and then blended.

[0095] The resin composition of the present invention preferably contains a compatibilizer in terms of antistatic properties and their durability, and solvent resistance. The compatibilizer may be one or more acid anhydride-modified polyolefins. The acid anhydride-modified polyolefin is a polymer in which an acid anhydride such as maleic anhydride is grafted onto a polyolefin.

[0096] The polyolefin portion of the acid anhydride modified polyolefin may be a polymer or copolymer of ethylene, propylene, α-olefin or diene, and examples of the α-olefin include 1-butene, 4-methyl-1-pentene, 1-pentene, 1-octene, 1-decene, 1-dodecene, etc., and examples of the diene include butadiene, isoprene, cyclopentadiene, 1,11-dodecadiene, etc. In addition to these, other copolymerization components may be included. More specifically, examples of the polyolefin include polyethylene, polypropylene, ethylene / propylene copolymer, ethylene / propylene / diene terpolymer, ethylene / 1-butene copolymer, ethylene / vinyl acetate copolymer, and mixtures thereof. Among these, from the viewpoints of antistatic property and its durability, and solvent resistance, polymerized or copolymerized ethylene, propylene, α-olefins having 4 to 12 carbon atoms, butadiene, and isoprene are preferred, polymerized or copolymerized ethylene, propylene, α-olefins having 4 to 8 carbon atoms, and butadiene are more preferred, and polymerized or copolymerized ethylene, propylene, and butadiene are even more preferred.

[0097] Examples of the acid anhydride include maleic anhydride and itaconic anhydride, with maleic anhydride being preferred from the standpoints of antistatic properties, their durability, and solvent resistance. The acid anhydride-modified polyolefin is preferably a maleic anhydride-modified polyolefin, more preferably a maleic anhydride-modified polypropylene, from the viewpoints of antistatic property and its durability, and solvent resistance. The acid anhydride-modified polyolefin is obtained by a grafting reaction of an acid anhydride such as maleic anhydride to a polyolefin by a conventionally known method, and various commercially available products may be used.

[0098] In the antistatic resin composition of the present invention, the content of the compatibilizer is preferably 0.01 to 30.0 parts by mass, more preferably 0.1 to 20.0 parts by mass, and even more preferably 0.5 to 15.0 parts by mass, relative to 100 parts by mass of the polyolefin resin, from the viewpoints of antistatic property and its durability, and solvent resistance.

[0099] The resin composition of the present invention may further contain a salt of a Group 2 element within a range that does not impair the effects of the present invention. Examples of salts of Group 2 elements include salts of organic acids or inorganic acids, and examples of Group 2 elements include beryllium, magnesium, calcium, strontium, barium, etc. Examples of organic acids include aliphatic monocarboxylic acids having 1 to 18 carbon atoms, such as formic acid, acetic acid, propionic acid, butyric acid, and lactic acid; aliphatic dicarboxylic acids having 1 to 12 carbon atoms, such as oxalic acid, malonic acid, succinic acid, fumaric acid, maleic acid, and adipic acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, and salicylic acid; and sulfonic acids having 1 to 20 carbon atoms, such as methanesulfonic acid, p-toluenesulfonic acid, dodecylbenzenesulfonic acid, and trifluoromethanesulfonic acid. Examples of inorganic acids include hydrochloric acid, hydrobromic acid, sulfuric acid, sulfurous acid, phosphoric acid, phosphorous acid, polyphosphoric acid, nitric acid, and perchloric acid.

[0100] The resin composition of the present invention may contain a surfactant within a range that does not impair the effects of the present invention. As the surfactant, a nonionic, anionic, cationic or amphoteric surfactant can be used.

[0101] Examples of the nonionic surfactant include polyethylene glycol-type nonionic surfactants such as higher alcohol ethylene oxide adducts, fatty acid ethylene oxide adducts, higher alkylamine ethylene oxide adducts, and polypropylene glycol ethylene oxide adducts; and polyhydric alcohol-type nonionic surfactants such as polyethylene oxide, fatty acid esters of glycerin, fatty acid esters of pentaerythritol, fatty acid esters of sorbitol or sorbitan, alkyl ethers of polyhydric alcohols, and fatty amides of alkanolamines.

[0102] Examples of the anionic surfactant include carboxylates such as alkali metal salts of higher fatty acids; sulfates such as higher alcohol sulfates and higher alkyl ether sulfates; sulfonates such as alkylbenzene sulfonates, alkyl sulfonates and paraffin sulfonates; and phosphates such as higher alcohol phosphates.

[0103] Examples of the cationic surfactant include quaternary ammonium salts such as alkyltrimethylammonium salts.

[0104] Examples of amphoteric surfactants include amino acid type amphoteric surfactants such as higher alkylaminopropionate salts, betaine type amphoteric surfactants such as higher alkyldimethylbetaine and higher alkyldihydroxyethylbetaine, and the like. These can be used alone or in combination of two or more kinds.

[0105] When a surfactant is added, the amount added is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 2 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0106] Furthermore, the resin composition of the present invention may contain a polymeric antistatic agent. For example, a known polymeric antistatic agent such as polyetheresteramide can be used as the polymeric antistatic agent. For example, a known polyetheresteramide can be used, which is a polyetheresteramide consisting of a polyoxyalkylene adduct of bisphenol A described in JP-A-7-10989. In addition, a block polymer having a repeating structure with 2 to 50 bond units between a polyolefin block and a hydrophilic polymer block can be used, which is an example of the block polymer described in U.S. Pat. No. 6,552,131.

[0107] When a polymer-type antistatic agent is blended, the blending amount is preferably 0.1 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass, per 100 parts by mass of the polyolefin resin. The resin composition of the present invention may contain thermoplastic resins other than the polyolefin resins described above, as long as the effects of the present invention are not impaired. Examples of other thermoplastic resins include halogen-containing resins such as polyvinyl chloride, polyvinylidene chloride, chlorinated polyethylene, chlorinated polypropylene, polyvinylidene fluoride, chlorinated rubber, vinyl chloride-vinyl acetate copolymer, vinyl chloride-ethylene copolymer, vinyl chloride-vinylidene chloride copolymer, vinyl chloride-vinylidene chloride-vinyl acetate terpolymer, vinyl chloride-acrylic acid ester copolymer, vinyl chloride-maleic acid ester copolymer, and vinyl chloride-cyclohexylmaleimide copolymer; petroleum resin, coumarone resin, polystyrene, polyvinyl acetate, acrylic resin, copolymers of styrene and / or α-methylstyrene with other monomers (e.g., maleic anhydride, phenylmaleimide, methyl methacrylate, butadiene, acrylonitrile, etc.) (e.g., AS resin, ABS resin, ACS resin, SBS resin, MBS resin, heat-resistant ABS resin, etc.); polymethyl methacrylate, polyvinyl alcohol, polyvinyl formal, polyvinyl butyral; polyethylene terephthalate, polybutyric acid ester, polyvinyl chloride ... Examples of the polyalkylene terephthalate include polyalkylene terephthalates such as polycyclohexanedimethylene terephthalate and polycyclohexanedimethylene terephthalate, polyalkylene naphthalates such as polyethylene naphthalate and polybutylene naphthalate, and aromatic polyesters such as polytetramethylene terephthalate; degradable aliphatic polyesters such as polyhydroxybutyrate, polycaprolactone, polybutylene succinate, polyethylene succinate, polylactic acid, polymalic acid, polyglycolic acid, polydioxane, and poly(2-oxetanone); polyamides such as polyphenylene oxide, polycaprolactam, and polyhexamethylene adipamide, polycarbonate, polycarbonate / ABS resin, branched polycarbonate, polyacetal, polyphenylene sulfide, polyurethane, cellulose resin, polyimide resin, polysulfone, polyphenylene ether, polyether ketone, polyether ether ketone, and liquid crystal polymer; and thermoplastic resins such as these, and blends thereof. Further examples of the thermoplastic resin include isoprene rubber, butadiene rubber, acrylonitrile-butadiene copolymer rubber, styrene-butadiene copolymer rubber, fluororubber, and silicone rubber.Further, thermoplastic elastomers are also included, examples of which include polystyrene-based thermoplastic elastomers, polyvinyl chloride-based thermoplastic elastomers, polyester-based thermoplastic elastomers, polyamide-based thermoplastic elastomers, polyurethane-based thermoplastic elastomers, etc. These thermoplastic resins may be used alone or in combination of two or more kinds. The thermoplastic resins may also be alloyed. Furthermore, various additives such as a phenol-based antioxidant, a phosphorus-based antioxidant, a thioether-based antioxidant, a hindered amine-based light stabilizer, and an ultraviolet absorber can be further added to the resin composition of the present invention within a range that does not impair the effects of the present invention, thereby stabilizing the resin composition of the present invention.

[0108] Examples of the phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol, 2,6-diphenyl-4-octadecyloxyphenol, distearyl (3,5-di-tert-butyl-4-hydroxybenzyl)phosphonate, 1,6-hexamethylenebis[(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid amide], 4,4'-thiobis(6-tert-butyl-m-cresol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-butyl-m-cresol, ... 2,2'-ethylidenebis(6-tert-butyl-m-cresol), 2,2'-ethylidenebis(4,6-di-tert-butylphenol), 2,2'-ethylidenebis(4-sec-butyl-6-tert-butylphenol), 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, 1,3,5-tris(2,6-dimethyl-3-hydroxy-4-tert-butylbenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanurate, diethyl)-2,4,6-trimethylbenzene, 2-tert-butyl-4-methyl-6-(2-acryloyloxy-3-tert-butyl-5-methylbenzyl)phenol, stearyl (3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tetrakis [3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate methyl]methane, thiodiethylene glycol bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 1,6-hexamethylene bis [(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 〕, bis[3,3-bis(4-hydroxy-3-tert-butylphenyl)butyric acid]glycol ester, bis[2-tert-butyl-4-methyl-6-(2-hydroxy-3-tert-butyl-5-methylbenzyl)phenyl]terephthalate, 1,3,5-tris[(3,5-ditert-butyl-4-hydroxyphenyl)propionyloxyethyl]isocyanurate, 3,9-bis[1,1-dimethyl-2-{(3-tert-butyl-4-hydroxy-5-methylphenyl)propionyloxy}ethyl]-2,4,8,10-tetraoxaspiro[5,5]undecane, triethylene glycol bis[(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], etc. The amount of these phenol-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, per 100 parts by mass of the polyolefin-based resin.

[0109] Examples of phosphorus-based antioxidants include trisnonylphenyl phosphite, tris[2-tert-butyl-4-(3-tert-butyl-4-hydroxy-5-methylphenylthio)-5-methylphenyl]phosphite, tridecyl phosphite, octyldiphenyl phosphite, di(decyl)monophenyl phosphite, di(tridecyl)pentaerythritol diphosphite, di(nonylphenyl)pentaerythritol diphosphite, bis(2,4-ditert-butylphenyl)pentaerythritol diphosphite, bis(2,6-ditert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4,6-tritert-butylphenyl)pentaerythritol diphosphite, bis(2,4-dicumylphenyl)pentaerythritol diphosphite, tetra(tridecyl)isopropylidenediphenol diphosphite, tetra(tridecyl)-4,4'-n-butylidenebis(2- tert-butyl-5-methylphenol) diphosphite, hexa(tridecyl)-1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane triphosphite, tetrakis(2,4-ditert-butylphenyl) biphenylene diphosphonite, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 2,2'-methylenebis(4,6-tert-butylphenyl)-2-ethylhexyl phosphite, 2 ,2'-methylenebis(4,6-tert-butylphenyl)-octadecyl phosphite, 2,2'-ethylidenebis(4,6-di-tert-butylphenyl)fluorophosphite, tris(2-[(2,4,8,10-tetrakis-tert-butyldibenzo[d,f][1,3,2]dioxaphosphepin-6-yl)oxy]ethyl)amine, phosphite of 2-ethyl-2-butylpropylene glycol and 2,4,6-tri-tert-butylphenol, etc. The amount of these phosphorus-based antioxidants to be added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0110] Examples of the thioether-based antioxidant include dialkyl thiodipropionates such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate, and pentaerythritol tetra(β-alkylthiopropionic acid) esters. The amount of these thioether-based antioxidants added is preferably 0.001 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, relative to 100 parts by mass of the polyolefin resin. Examples of the hindered amine light stabilizer include 2,2,6,6-tetramethyl-4-piperidyl stearate, 1,2,2,6,6-pentamethyl-4-piperidyl stearate, 2,2,6,6-tetramethyl-4-piperidyl benzoate, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1-octoxy-2,2,6,6-tetramethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2 ,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, bis(2,2,6,6-tetramethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)·di(tridecyl)-1,2,3,4-butanetetracarboxylate, bis(1,2,2,4,4-pentamethyl-4-piperidyl)-2-butyl-2-(3,5-ditert-butyl-4-hydroxyethyl) dibenzyl)malonate, 1-(2-hydroxyethyl)-2,2,6,6-tetramethyl-4-piperidinol / diethyl succinate polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-morpholino-s-triazine polycondensate, 1,6-bis(2,2,6,6-tetramethyl-4-piperidylamino)hexane / 2,4-dichloro-6-tert-octylamino-s-triazine polycondensate, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4 -piperidyl)amino)-s-triazin-6-yl]-1,5,8,12-tetraazadodecane, 1,5,8,12-tetrakis[2,4-bis(N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl]-1,5,8-12-tetraazadodecane, 1,6,11-tris[2,4-bis(N-butyl-N-(2,2,6,6-tetramethyl-4-piperidyl)amino)-s-triazin-6-yl]aminoundecane, 1,6,11-tris[2,4-bis(N-butyl-N-(1,2,2,6,Examples of the hindered amine compounds include 6-pentamethyl-4-piperidyl)amino)-s-triazin-6-yl)aminoundecane. The amount of these hindered amine-based light stabilizers added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin-based resin.

[0111] Examples of the ultraviolet absorber include 2-hydroxybenzophenones such as 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-octoxybenzophenone, and 5,5'-methylenebis(2-hydroxy-4-methoxybenzophenone); 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2'-hydroxy-3',5'- 2-(2'-hydroxyphenyl)benzotriazoles such as 2-(2'-hydroxy-5'-tert-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-dicumylphenyl)benzotriazole, 2,2'-methylenebis(4-tert-octyl-6-(benzotriazolyl)phenol), 2-(2'-hydroxy-3'-tert-butyl-5'-carboxyphenyl)benzotriazole; phenyl Benzoates such as ricinate, resorcinol monobenzoate, 2,4-ditert-butylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, 2,4-ditert-amylphenyl-3,5-ditert-butyl-4-hydroxybenzoate, hexadecyl-3,5-ditert-butyl-4-hydroxybenzoate; substituted oxanilides such as 2-ethyl-2'-ethoxyoxanilide, 2-ethoxy-4'-dodecyloxanilide; ethyl-α-cyano-β,β-diphenylacrylate, methyl and triaryl triazines such as 2-(2-hydroxy-4-octoxyphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine, 2-(2-hydroxy-4-methoxyphenyl)-4,6-diphenyl-s-triazine, and 2-(2-hydroxy-4-propoxy-5-methylphenyl)-4,6-bis(2,4-di-tert-butylphenyl)-s-triazine. The amount of these ultraviolet absorbers to be added is preferably 0.001 to 30 parts by mass, more preferably 0.05 to 10 parts by mass, based on 100 parts by mass of the polyolefin resin.

[0112] Furthermore, if necessary, it is preferable to add a known neutralizing agent to neutralize the residual catalyst in the polyolefin resin. Examples of the neutralizing agent include fatty acid metal salts such as calcium stearate, lithium stearate, and sodium stearate, and fatty acid amide compounds such as ethylene bis(stearamide), ethylene bis(12-hydroxystearamide), and stearic acid amide, and these neutralizing agents may be used in combination. Furthermore, the resin composition of the present invention may further contain, as necessary, metal salts of carboxylates such as sodium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, lithium-2,2'-methylenebis(4,6-di-tert-butylphenyl)phosphate, aluminum hydroxybis[2,2'methylenebis(4,6-di-tert-butylphenyl)phosphate], sodium benzoate, aluminum 4-tert-butylbenzoate, sodium adipate, and disodium bicyclo[2.2.1]heptane-2,3-dicarboxylate, dibenzylidene sorbitol, bis(methylbenzylidene)sorbitol, bis(3,4-dimethylbenzyl)phosphate, and the like.

[0043] Nucleating agents such as aromatic carboxylic acid metal salts, alicyclic alkyl carboxylic acid metal salts, aluminum p-tert-butylbenzoate, aromatic phosphate metal salts, dibenzylidene sorbitols, and the like may also be blended.

[0113] Furthermore, to the resin composition of the present invention, metal soaps, hydrotalcites, triazine ring-containing compounds, metal hydroxides, phosphate ester-based flame retardants, condensed phosphate ester-based flame retardants, phosphate-based flame retardants, inorganic phosphorus-based flame retardants, (poly)phosphate-based flame retardants, halogen-based flame retardants, silicon-based flame retardants, antimony oxides such as antimony trioxide, inorganic flame retardant assistants, organic flame retardant assistants, anti-drip agents, fillers, pigments, lubricants, foaming agents, and the like may be added, if necessary.

[0114] Examples of the triazine ring-containing compound include melamine, ammeline, benzguanamine, acetoguanamine, phthalodiguanamine, melamine cyanurate, melamine pyrophosphate, butylenediguanamine, norbornenediguanamine, methylenediguanamine, ethylenedimelamine, trimethylenedimelamine, tetramethylenedimelamine, hexamethylenedimelamine, and 1,3-hexylenedimelamine.

[0115] Examples of the metal hydroxide include magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, zinc hydroxide, and Kismer 5A (magnesium hydroxide: manufactured by Kyowa Chemical Industry Co., Ltd.).

[0116] Examples of the phosphate ester-based flame retardants include trimethyl phosphate, triethyl phosphate, tributyl phosphate, tributoxyethyl phosphate, trischloroethyl phosphate, trisdichloropropyl phosphate, triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, trixylenyl phosphate, octyl diphenyl phosphate, xylenyl diphenyl phosphate, trisisopropylphenyl phosphate, 2-ethylhexyl diphenyl phosphate, t-butylphenyl diphenyl phosphate, bis-(t-butylphenyl)phenyl phosphate, tris-(t-butylphenyl)phosphate, isopropylphenyl diphenyl phosphate, bis-(isopropylphenyl)diphenyl phosphate, and tris-(isopropylphenyl)phosphate.

[0117] Examples of the condensed phosphate ester flame retardants include 1,3-phenylene bis(diphenyl phosphate), 1,3-phenylene bis(dixylenyl phosphate), bisphenol A bis(diphenyl phosphate), and the like.

[0118] Examples of the (poly)phosphate-based flame retardant include ammonium salts and amine salts of (poly)phosphoric acids, such as ammonium polyphosphate, melamine polyphosphate, piperazine polyphosphate, melamine pyrophosphate, and piperazine pyrophosphate.

[0119] Examples of inorganic flame retardant auxiliary agents include inorganic compounds such as titanium oxide, aluminum oxide, magnesium oxide, hydrotalcite, talc, and montmorillonite, and surface-treated products thereof, and various commercially available products such as TIPAQUE R-680 (titanium oxide: manufactured by Ishihara Sangyo Kaisha), Kyowamag 150 (magnesium oxide: manufactured by Kyowa Chemical Industry Co., Ltd.), DHT-4A (hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.), and Alcamizer 4 (zinc-modified hydrotalcite: manufactured by Kyowa Chemical Industry Co., Ltd.) can be used. Examples of organic flame retardant auxiliary agents include pentaerythritol.

[0120] Furthermore, the resin composition of the present invention may contain additives that are usually used in polyolefin resins, such as crosslinking agents, antifogging agents, plate-out inhibitors, surface treatment agents, plasticizers, lubricants, flame retardants, fluorescent agents, antifungal agents, bactericides, foaming agents, metal deactivators, release agents, pigments, processing aids, antioxidants, light stabilizers, etc., as necessary, within the range that does not impair the effects of the present invention.

[0121] The method for producing the resin composition of the present invention is not particularly limited, and it is sufficient to blend one or more polymer compounds (E) as component (X), one or more selected from the group consisting of alkali metal salts (F) and ionic liquids (G) as component (Y), and other optional components with a polyolefin resin, and any method that is commonly used can be used for the blending method. For example, there is a method of dry blending using a blender or Henschel mixer, or a method of melt blending using an extruder, Banbury mixer, kneader, or the like.

[0122] The polymer compound (E) which is the component (X) may be added as it is, or may be added after impregnating it into a carrier as necessary. To impregnate the carrier, it may be heated and mixed as it is, or it may be diluted with an organic solvent as necessary, impregnated into the carrier, and then the solvent may be removed. As such a carrier, a material known as a filler or bulking agent for synthetic resins, or a flame retardant or light stabilizer which is solid at room temperature may be used, and examples thereof include calcium silicate powder, silica powder, talc powder, alumina powder, titanium oxide powder, or a carrier whose surface is chemically modified, and the flame retardants and antioxidants listed above which are solid, etc. Among these carriers, a carrier whose surface is chemically modified is preferred, and a silica powder whose surface is chemically modified is more preferred. These carriers preferably have an average particle size of 0.1 to 100 μm, and more preferably 0.5 to 50 μm.

[0123] Furthermore, as a method for blending the polymer compound (E) as component (X) into the polyolefin resin, the polymer compound (E) may be synthesized and blended while kneading the block polymer (C) and the epoxy compound (D) having two or more epoxy groups into the resin component, and at that time, one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), as component (Y), may be blended simultaneously. Alternatively, the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the resin component may be mixed during molding such as injection molding to obtain a molded product. Furthermore, a masterbatch of the polymer compound (E), one or more types selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G), and the polyolefin resin may be produced in advance, and this masterbatch may be blended. Furthermore, the polymer compound (E) and one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) may be mixed in advance and then blended with the polyolefin resin. Alternatively, the polymer compound (E) synthesized by adding one or more selected from the group consisting of the alkali metal salt (F) and the ionic liquid (G) during the synthesis reaction may be blended with the polyolefin resin.

[0124] Next, the transport container of the present invention will be described. The antistatic resin composition of the present invention is molded to obtain a transport container. The molding method is not particularly limited and may be a known method. Examples of the molding method include extrusion processing, calendar processing, injection molding, roll, compression molding, blow molding, and rotational molding.

[0125] From the viewpoints of antistatic property and its durability, and solvent resistance, the transport container of the present invention is preferably a transport container for liquids, and more preferably a transport container for flammable liquids. In addition, the transport container of the present invention is preferably a bulk container (also called an intermediate bulk container or IBC container) from the viewpoints of antistatic property, its durability, and solvent resistance. The transport container of the present invention is preferably used for transporting and storing chemical raw materials, industrial chemicals, industrial materials, solvents, resins, minerals, feed, fertilizers, grains, chemicals, food, medicines, and the like.

[0126] The transport container of the present invention can be used for transporting and storing liquids or powders and granular materials, and in particular, the transport container of the present invention is preferably used for transporting and storing liquids such as solvents because of its antistatic properties and their durability, and solvent resistance, and is even more preferably used for transporting and storing flammable liquids.

[0127] Examples of flammable liquids include organic solvents, and examples of organic solvents include alcohol-based solvents, diol-based solvents, ketone-based solvents, ester-based solvents, ether-based solvents, aliphatic or alicyclic hydrocarbon-based solvents, aromatic hydrocarbon-based solvents, hydrocarbon solvents having a cyano group, petroleum-based solvents, halogen-based solvents, and other solvents.

[0128] Examples of alcohol-based solvents include methanol, ethanol, propanol, isopropanol, 1-butanol, isobutanol, 2-butanol, tertiary butanol, pentanol, isopentanol, 2-pentanol, neopentanol, tertiary pentanol, hexanol, 2-hexanol, heptanol, 2-heptanol, octanol, 2-ethylhexanol, 2-octanol, cyclopentanol, cyclohexanol, cycloheptanol, methylcyclopentanol, methylcyclohexanol, methylcycloheptanol, benzyl alcohol, ethylene glycol monoacetate, and ethylene glycol monoethyl ether. Examples of the monoglycerin-containing alkyl ether include ethylene glycol monophenyl ether, ethylene glycol monobutyl ether, ethylene glycol monomethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol monobutyl ether, 2-(2-methoxyethoxy)ethanol, 2-(N,N-dimethylamino)ethanol, 3-(N,N-dimethylamino)propanol, and the like. Also usable are rubbing alcohol and the like.

[0129] Examples of diol solvents include ethylene glycol, propylene glycol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, neopentyl glycol, isoprene glycol (3-methyl-1,3-butanediol), 1,2-hexanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 1,2-octanediol, octanediol (2-ethyl-1,3-hexanediol), 2-butyl-2-ethyl-1,3-propanediol, 2,5-dimethyl-2,5-hexanediol, 1,2-cyclohexanediol, 1,4-cyclohexanediol, and 1,4-cyclohexanedimethanol. Examples of the ketone solvent include acetone, ethyl methyl ketone, methyl butyl ketone, methyl isobutyl ketone, ethyl butyl ketone, dipropyl ketone, diisobutyl ketone, methyl amyl ketone, cyclohexanone, and methyl cyclohexanone.

[0130] Examples of ester-based solvents include methyl formate, ethyl formate, methyl acetate, ethyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, tert-butyl acetate, amyl acetate, isoamyl acetate, tert-amyl acetate, phenyl acetate, methyl propionate, ethyl propionate, isopropyl propionate, butyl propionate, isobutyl propionate, sec-butyl propionate, tert-butyl propionate, amyl propionate, isoamyl propionate, tert-amyl propionate, phenyl propionate, methyl 2-ethylhexanoate, Ethyl 2-ethylhexanoate, Propyl 2-ethylhexanoate, Isopropyl 2-ethylhexanoate, Butyl 2-ethylhexanoate, Methyl lactate, Ethyl lactate, Methyl methoxypropionate, Methyl ethoxypropionate, Ethyl methoxypropionate, Ethyl ethoxypropionate, Ethylene glycol monomethyl ether acetate, Diethylene glycol monomethyl ether acetate, Ethylene glycol monoethyl ether acetate, Ethylene glycol monopropyl ether acetate, Ethylene glycol monoisopropyl ether acetate, ethylene glycol monobutyl ether acetate, ethylene glycol mono-sec-butyl ether acetate, ethylene glycol monoisobutyl ether acetate, ethylene glycol mono-tert-butyl ether acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, propylene glycol monoisopropyl ether acetate, propylene glycol monobutyl ether acetate, propylene glycol mono-sec-butyl ether acetate, propylene glycol monoisobutyl ether acetate, propylene glycol mono-tert-butyl ether acetate, butylene glycol monomethyl ether acetate, butylene glycol monoethyl ether acetate, butylene glycol monopropyl ether acetate, butylene glycol monoisopropyl ether acetate, butylene glycol monobutyl ether acetate, butylene glycol mono-sec-butyl ether acetate, butylene glycol monoisobutyl ether acetate,butylene glycol mono-tert-butyl ether acetate, methyl acetoacetate, ethyl acetoacetate, methyl oxobutanoate, ethyl oxobutanoate, γ-lactone, δ-lactone, etc. Examples of the ether solvent include tetrahydrofuran, tetrahydropyran, morpholine, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, dibutyl ether, diethyl ether, and dioxane.

[0131] Examples of the aliphatic or alicyclic hydrocarbon solvent include pentane, hexane, cyclohexane, methylcyclohexane, dimethylcyclohexane, ethylcyclohexane, heptane, octane, decalin, and solvent naphtha. Examples of aromatic hydrocarbon solvents include benzene, toluene, ethylbenzene, xylene, mesitylene, diethylbenzene, cumene, isobutylbenzene, cymene, and tetralin.

[0132] Petroleum-based solvents include mineral spirits, kerosene, thinner, and the like. Examples of halogen-based solvents include methylene chloride, chloroform, 1,2-dichloroethane, trichloroethylene, and tetrachloroethylene.

[0133] Examples of hydrocarbon solvents having a cyano group include acetonitrile, 1-cyanopropane, 1-cyanobutane, 1-cyanohexane, cyanocyclohexane, cyanobenzene, 1,3-dicyanopropane, 1,4-dicyanobutane, 1,6-dicyanohexane, 1,4-dicyanocyclohexane, and 1,4-dicyanobenzene.

[0134] Other organic solvents include N-methyl-2-pyrrolidone, dimethylsulfoxide, dimethylformamide, dimethylacetamide, sulfolane, acetic acid, acetic anhydride, and glacial acetic acid. In the present invention, the organic solvent also includes liquid fuels, and it is also preferable to use the organic solvent in a transport container for these fuels.

[0135] Examples of fuels include petroleum, shale oil, kerosene, gasoline, diesel, heavy oil, jet fuel, naphtha, benzine, liquefied natural gas, liquefied petroleum gas, liquefied propane gas, and liquefied shale gas.

[0136] In the present invention, the organic solvent also includes oils of natural origin, such as vegetable oils and animal oils. These oils include both edible and industrial oils. Examples of edible oils include canola oil, coconut oil, corn oil, cottonseed oil, olive oil, palm oil, palm kernel oil, peanut oil, rapeseed oil, safflower oil, sesame oil, soybean oil, sunflower oil, almond oil, linseed oil, grapeseed oil, perilla oil, rice oil, beef tallow, lard, and fish oil, and examples of industrial oils include tung oil, linseed oil, and castor oil.

[0137] These organic solvents may be used alone or in combination of two or more. In addition, components other than the organic solvent may be dissolved or mixed in. Furthermore, water may be mixed in. The transport container of the present invention is also preferable as a transport container for waste liquids such as industrial waste liquids containing the above organic solvents. EXAMPLES

[0138] The present invention will be described in more detail below using examples, but the present invention is not limited to these. According to the following production example, the polymer compound (E) which is the component (X) of the present invention was produced. In the following production example, the number average molecular weight of the polyether (b) was calculated by the following <Method of calculating number average molecular weight from hydroxyl value>, and the number average molecular weights of the polyester (a) and the block polymer (C) were calculated by the following <Method of measuring number average molecular weight in terms of polystyrene>. The molecular weight of the polypropylene glycol diglycidyl ether was calculated from the epoxy equivalent.

[0139] <Calculation method of number average molecular weight from hydroxyl value> The hydroxyl value was measured by the following hydroxyl value measurement method, and the number average molecular weight (hereinafter also referred to as "Mn") was determined by the following formula. Number average molecular weight = (56110 x 2) / hydroxyl value <Hydroxyl value measurement method> Reagent A (acetylating agent) (1) Triethyl phosphate 1560mL (2) Acetic anhydride, 193 mL (3) Perchloric acid (60%) 16g Mix the above reagents in the order of (1) → (2) → (3). Reagent B Mix pyridine and pure water in a volume ratio of 3:1. Reagent C Add 2 to 3 drops of phenolphthalein solution to 500 mL of isopropyl alcohol and neutralize with 1N KOH aqueous solution.

[0140] First, weigh out 2 g of sample into a 200 mL Erlenmeyer flask, add 10 mL of triethyl phosphate, and heat to dissolve. Add 15 mL of Reagent A, plug with a stopper, and shake vigorously. Add 20 mL of Reagent B, plug with a stopper, and shake vigorously. Add 50 mL of Reagent C. Titrate with 1N KOH aqueous solution and calculate using the formula below. Hydroxyl value [mgKOH / g] = 56.11 × f × (TB) / S f: Factor of 1N-KOH solution B: Blank test titration volume [mL] T: Test titer [mL] S: Sample amount [g]

[0141] <Method for measuring number average molecular weight based on polystyrene conversion> The number average molecular weight (hereinafter also referred to as "Mn") was measured by gel permeation chromatography (GPC). The measurement conditions for Mn were as follows: Equipment: GPC equipment manufactured by JASCO Corporation Solvent: Chloroform Reference material: Polystyrene Detector: Differential refractometer (RI detector) Column stationary phase: Showa Denko Co., Ltd. Shodex LF-804 Column temperature: 40℃ Sample concentration: 1mg / 1mL Flow rate: 0.8mL / min. Injection volume: 100μL

[0142] [Production Example 1] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-1. The number average molecular weight Mn of the obtained polyester (a)-1 was 2931.

[0143] Next, 205 g of the obtained polyester (a)-1, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-1 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-1 having a structure with carboxyl groups at both ends was 22109.

[0144] To 392 g of the obtained block polymer (C)-1 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-1.

[0145] [Production Example 2] 207 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 153 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 32 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 20 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.4 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-2 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-2 having a structure with carboxyl groups at both ends was 22302.

[0146] To 429 g of the obtained block polymer (C)-2 having a structure with carboxyl groups at both ends, 3.9 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 434 g of polymer compound (E)-2.

[0147] [Production Example 3] 196 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 96 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 80 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 50 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-3 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-3 having a structure having carboxyl groups at both ends was 21134.

[0148] To 376 g of the obtained block polymer (C)-3 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and polymerization was carried out under reduced pressure at 240°C for 3 hours, to obtain 380 g of polymer compound (E)-3.

[0149] [Production Example 4] 209 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 163 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 24 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 15 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.5 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-4 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-4 having a structure with carboxyl groups at both ends was 22485.

[0150] To 396 g of the obtained block polymer (C)-4 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-4.

[0151] [Production Example 5] 189 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 57 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 112 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 70 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-5 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-5 having a structure having carboxyl groups at both ends was 20372.

[0152] To 396 g of the obtained block polymer (C)-5 having a structure with carboxyl groups at both ends, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 400 g of polymer compound (E)-5.

[0153] [Production Example 6] 202 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 2000 as compound (b1)-2 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 2000 as compound (b2)-2 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-6 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-6 having a structure with carboxyl groups at both ends was 12631. To 397 g of the obtained block polymer (C)-6 having a structure with carboxyl groups at both ends, 6.3 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 405 g of polymer compound (E)-6.

[0154] [Production Example 7] 200 g of polyester (a)-1 obtained in the same manner as in Production Example 1, 135 g of polyethylene glycol having a number average molecular weight of 4000 as compound (b1)-3 of polyether (b) having hydroxyl groups at both ends, 45 g of polytetramethylene glycol having a number average molecular weight of 4000 as compound (b2)-3 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.2 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain block polymer (C)-7 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-7 having a structure with carboxyl groups at both ends was 25243.

[0155] To 398 g of the obtained block polymer (C)-7 having a structure with carboxyl groups at both ends, 3.2 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 402 g of polymer compound (E)-7.

[0156] [Production Example 8] A separable flask was charged with 97 g of 1,4-cyclohexanedimethanol, 112 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the temperature was gradually raised from 170°C to 215°C while polymerization was continued at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-2. The number average molecular weight Mn of the obtained polyester (a)-2 was 2053.

[0157] Next, 185 g of the obtained polyester (a)-2, 185 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 51 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.7 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-8 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-8 having a structure with carboxyl groups at both ends was 18,600.

[0158] To 461 g of the obtained block polymer (C)-8 having a structure with carboxyl groups at both ends, 5.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 467 g of polymer compound (E)-8.

[0159] [Production Example 9] A separable flask was charged with 135 g of 1,4-cyclohexanedimethanol, 143 g of adipic acid, 1.5 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-3. The number average molecular weight Mn of the obtained polyester (a)-3 was 5347.

[0160] Next, 244 g of the obtained polyester (a)-3, 94 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 26 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-9 having a structure with carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-9 having a structure with carboxyl groups at both ends was 31773.

[0161] To 401 g of the obtained block polymer (C)-9 having a structure with carboxyl groups at both ends, 2.6 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 404 g of polymer compound (E)-9.

[0162] [Production Example 10] To 401 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 1.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 304, epoxy equivalent 200 g / eq) as epoxy compound (D)-2 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 403 g of polymer compound (E)-10.

[0163] [Production Example 11] To 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends obtained in the same manner as in Production Example 1, 2.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 769, epoxy equivalent 471 g / eq) as epoxy compound (D)-3 was added, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-11.

[0164] [Production Example 12] 391 g of block polymer (C)-1 having a structure with carboxyl groups at both ends, obtained in the same manner as in Production Example 1, was charged with 2.1 g of bisphenol F diglycidyl ether (epoxy equivalent: 170 g / eq) as epoxy compound (D)-4, and the mixture was polymerized at 240°C for 3 hours under reduced pressure, thereby obtaining 394 g of polymer compound (E)-12.

[0165] [Production Example 13] A separable flask was charged with 124 g of hydrogenated bisphenol A, 84 g of adipic acid, 0.1 g of phthalic anhydride, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adeka STAB AO-60, manufactured by ADEKA Corporation), and the mixture was gradually heated from 170°C to 215°C while undergoing polymerization at normal pressure for 4 hours, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-4. The number average molecular weight Mn of the obtained polyester (a)-4 was 2922.

[0166] Next, 190 g of the obtained polyester (a)-4, 133 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 37 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of antioxidant (Adekastab AO-60), and 3.1 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-10 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-10 having a structure having carboxyl groups at both ends was 21500.

[0167] To 391 g of the obtained block polymer (C)-10 having a structure with carboxyl groups at both ends, 3.7 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-13.

[0168] [Production Example 14] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 122 g of adipic acid, and 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, Adekastab AO-60, manufactured by ADEKA Corporation), and the mixture was polymerized at normal pressure for 4 hours while gradually increasing the temperature from 170°C to 215°C, and then at 215°C under reduced pressure for 3 hours to obtain polyester (a)-5. The number average molecular weight Mn of the obtained polyester (a)-5 was 2931.

[0169] Next, 206 g of the obtained polyester (a)-5, 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the ratio of polytetramethylene glycol (b2) is 25 mol% relative to the total mole number of polyethylene glycol and polytetramethylene glycol), 0.4 g of an antioxidant (Adekastab AO-60), and 3.3 g of zirconium octylate were charged, and the temperature was gradually increased from 215 ° C. to 240 ° C. for 7 hours under reduced pressure to obtain a block polymer (C)-11 having a structure having carboxyl groups at both ends. The number average molecular weight Mn of this block polymer (C)-11 having a structure having carboxyl groups at both ends was 22109.

[0170] To 392 g of the obtained block polymer (C)-11 having a structure with carboxyl groups at both ends, 4.4 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours, to obtain 396 g of polymer compound (E)-14.

[0171] [Production Example 15] A separable flask was charged with 111 g of 1,4-cyclohexanedimethanol, 123 g of adipic acid, 0.1 g of phthalic anhydride, 0.4 g of an antioxidant (tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyloxymethyl]methane, ADK STAB AO-60, manufactured by ADEKA CORPORATION), 144 g of polyethylene glycol having a number average molecular weight of 3650 as compound (b1)-1 of polyether (b) having hydroxyl groups at both ends, and 40 g of polytetramethylene glycol having a number average molecular weight of 3042 as compound (b2)-1 (the proportion of polytetramethylene glycol (b2) was 25 mol % relative to the total mole number of polyethylene glycol and polytetramethylene glycol), and polymerization was carried out at normal pressure for 4 hours while gradually increasing the temperature from 170° C. to 215° C. 3.5 g of zirconium octylate was added, and polymerization was carried out under reduced pressure for 7 hours while gradually increasing the temperature from 215° C. to 240° C. to obtain a polymer. The number average molecular weight Mn of the obtained polymer was 22,109.

[0172] To 392 g of the obtained polymer, 4.0 g of polypropylene glycol diglycidyl ether (number average molecular weight 530, epoxy equivalent 300 g / eq) as epoxy compound (D)-1 was added, and the mixture was polymerized under reduced pressure at 240°C for 3 hours to obtain 396 g of polymer compound (E)-15.

[0173] [Examples 1 to 20, Comparative Examples 1 to 4] Test pieces were obtained under the test piece preparation conditions shown below using resin compositions blended based on the compounding amounts (parts by mass) shown in Tables 1 to 5 below. Using the obtained test pieces, surface resistivity (SR value) was measured according to the measurement method shown below, and antistatic properties and their durability were evaluated. Furthermore, a solvent resistance evaluation test was performed according to the test method shown below. The results are shown in Tables 1 to 5. Furthermore, in the same manner as in the examples, measurements and evaluations were performed using comparative antistatic agent-1 in the compounding amounts shown in Tables 1 to 5. The results are shown in Tables 1 to 5.

[0174] <Test piece preparation conditions> The resin compositions blended based on the compounding amounts shown in Tables 1 to 5 below were granulated at 230°C and 6 kg / hour using a twin-screw extruder (PCM30, 60 mesh) manufactured by Ikegai Corp. to obtain pellets. The obtained pellets were molded using a horizontal injection molding machine (NEX80: manufactured by Nissei Plastic Industrial Co., Ltd.) under processing conditions of a resin temperature of 230°C and a mold temperature of 40°C to obtain test pieces (100 mm x 100 mm x 3 mm).

[0175] <Surface resistivity (SR value) measurement method> The obtained test pieces were stored immediately after molding under conditions of a temperature of 25°C and a humidity of 50% RH, and after storage for 1 day and 30 days after molding, the surface resistivity (Ω / □) was measured under the same atmosphere under conditions of an applied voltage of 100 V and an application time of 1 minute using a Hiresta-UX Hiresta (MCP-HT800) resistance meter manufactured by Mitsubishi Chemical Analytech Co., Ltd. Measurements were performed at 5 points on each of 5 test pieces, and the average value was calculated. Surface resistivity (Ω / □) is >1×10 16 If it is Ω / □, measurement is not possible and it is considered Over Range (OR).

[0176] <Solvent resistance evaluation test> The obtained test piece was immersed in an 80 vol% aqueous ethanol solution, octane, and toluene. After 14 days, the test piece was removed from each solvent and dried in a 60°C air drying oven. The dried test piece was left to stand for 24 hours in a thermo-hygrostat chamber adjusted to a temperature of 25°C and a humidity of 60%, and then, in the same atmosphere, the surface resistivity (Ω / □) was measured using a Hiresta-UX Hiresta (MCP-HT800) resistance meter manufactured by Mitsubishi Chemical Analytech Co., Ltd. under the conditions of an applied voltage of 100V and an application time of 1 minute. The measurement was performed on five test pieces at five points per piece, and the average value was calculated. Surface resistivity (Ω / □) is >1×10 16 If it is Ω / □, measurement is not possible and it is considered Over Range (OR).

[0177] [Table 1]

[0178] *1: High density polyethylene: Made by Japan Polyethylene Co., Ltd., product name Novatec HD HJ560 (melt flow rate = 7g / 10min) *2:NaDBS: Sodium dodecylbenzenesulfonate *3: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *4: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *5: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16

[0179] [Table 2]

[0180] *1: High density polyethylene: Made by Japan Polyethylene Co., Ltd., product name Novatec HD HJ560 (melt flow rate = 7g / 10min) *2:NaDBS: Sodium dodecylbenzenesulfonate *3: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *4: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *5: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16

[0181] [Table 3]

[0182] *1: High density polyethylene: Made by Japan Polyethylene Co., Ltd., product name Novatec HD HJ560 (melt flow rate = 7g / 10min) *2:NaDBS: Sodium dodecylbenzenesulfonate *3: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *4: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *5: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16

[0183] [Table 4]

[0184] *1: High density polyethylene: Made by Japan Polyethylene Co., Ltd., product name Novatec HD HJ560 (melt flow rate = 7g / 10min) *2:NaDBS: Sodium dodecylbenzenesulfonate *3: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *4: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *5: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16

[0185] [Table 5]

[0186] *1: High density polyethylene: Made by Japan Polyethylene Co., Ltd., product name Novatec HD HJ560 (melt flow rate = 7g / 10min) *2:NaDBS: Sodium dodecylbenzenesulfonate *3: C2mimDBS: 1-ethyl-3-methylimidazolium dodecylbenzenesulfonate *4: (b2) / [(b1)+(b2)]: The ratio of polytetramethylene glycol to the total number of moles of polyethylene glycol (b1) and polytetramethylene glycol (b2). Molar %. *5: Comparative antistatic agent-1: Polyether ester amide-based antistatic agent, manufactured by BASF, product name Irgastat P-16

[0187] From the above, it is found that the antistatic resin composition of the present invention has excellent antistatic properties and their durability, and is also excellent in solvent resistance. Therefore, the antistatic resin composition of the present invention is suitable for transport containers, particularly for transport containers for liquids (especially flammable liquids) and bulk containers.

Claims

1. An antistatic resin composition comprising 2 to 35 parts by mass of the following component (X) and 0.1 to 5.0 parts by mass of the following component (Y) relative to 100 parts by mass of a polyolefin resin: Component (X): An antistatic agent containing one or more polymeric compounds (E) obtained by reacting a diol (a1), a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups, wherein the polyether (b) having hydroxyl groups at both ends is polyethylene glycol (b1) and polytetramethylene glycol (b2), and the proportion of polytetramethylene glycol (b2) is 10 to 80 mol % based on the total molar number of the polyethylene glycol (b1) and polytetramethylene glycol (b2). Component (Y): one or more members selected from the group consisting of an alkali metal salt (F) and an ionic liquid (G).

2. 2. The antistatic resin composition according to claim 1, wherein the polymer compound (E) is obtained by reacting a polyester (a) obtained by reacting a diol (a1) with a dicarboxylic acid (a2), a polyether (b) having hydroxyl groups at both ends, and an epoxy compound (D) having two or more epoxy groups.

3. 3. The antistatic resin composition according to claim 2, wherein the polymer compound (E) has a polyester block (A) composed of the polyester (a) and a polyether block (B) composed of the polyether (b), and has a structure in which the blocks are bonded via an ester bond or an ether bond formed by a reaction between a hydroxyl group or a carboxyl group at an end of the polyester (a), a hydroxyl group at an end of the polyether (b), and an epoxy group of the epoxy compound (D) or a hydroxyl group formed by a reaction of an epoxy group.

4. 4. The antistatic resin composition according to claim 3, wherein the polymer compound (E) has a structure in which a block polymer (C) having carboxyl groups at both ends thereof, which is formed by repeatedly and alternately bonding the polyester block (A) and the polyether block (B) via ester bonds, and the epoxy compound (D) are bonded via ester bonds.

5. 2. The antistatic resin composition according to claim 1, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

6. 3. The antistatic resin composition according to claim 2, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

7. 4. The antistatic resin composition according to claim 3, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

8. 5. The antistatic resin composition according to claim 4, wherein the epoxy compound (D) of the polymer compound (E) is polypropylene glycol diglycidyl ether.

9. A transport container formed from the antistatic resin composition according to any one of claims 1 to 8.

10. 10. The transport container of claim 9, wherein the transport container is for a liquid.

11. 11. The transport container of claim 10, wherein the liquid is a flammable liquid.

12. 10. The shipping container of claim 9, wherein the shipping container is a bulk container.

Citation Information

Patent Citations

  • Plastic containers and moldings with good antistatic properties produced by blow molding

    JP2003526583A

  • Bundling aids and bundling methods for framed containers

    JP2017518926A